The Crime of Marital Adultery and Methods of Proving it in Islamic Jurisprudence and Iraqi Legislation - Haider, Dr. Nouri Hama Saeed (Journal of Legal and Political Studies, 2018)
In this research, I discussed the crime of adultery and the methods of proving it in Islamic jurisprudence and its comparison with the various Iraqi legislations and the ways in which this crime can be proved in the absence of confession, and this research consists of a number of chapters. In the first chapter, I will define adultery linguistically, legally, and from a sharia point of view. I will clarify the meaning of the term adultery. and then, this work will illustrate the course of the Sharia and the law in regard to adultery as an absolute crime or only in certain cases. and I will explain the ruling on sharia law and the law on this disgraceful act. The second section will be devoted to clarifying the position of the Iraqi legislator on this crime as stipulated in the Iraqi Penal Code, Criminal Procedure Code, and Personal Status Law, with emphasis on amendments to the articles on this crime in The Kurdistan Regional Government, and elucidate the vital differences between infidelity and adultery. In the third chapter, I will study methods of proving adultery in Islamic jurisprudence and Iraqi law, whether by confession or testimony of witnesses, or by the available scientific means. I will also, make reference to and specify the position of contemporary jurists and Islamic jurisprudence assemblies and Iraqi law on using these methods to prove adultery that was originally stipulated in the the Evidence Act to prove civil cases. In the fourth Chapter, I look at ways to reduce the crime of adultery by strengthening the religious conscience and penal legislation, without forgetting to quickly address some of its causes. This is my hope and Allah is the way to go ...
Keywords: Islamic jurisprudence; adultery; sharia law; religious conscience